2020
DOI: 10.1038/s41598-020-68648-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of resveratrol in wild Arachis species adds new value to this overlooked genetic resource

Abstract: Genus Arachis comprises 82 species distributed into nine taxonomic sections. Most Arachis species are wild and those from Arachis section have been evaluated for many traits, since they can be used in peanut breeding. Most of the remaining species have been neglected and understudied. Recently, resveratrol content and expression of a resveratrol synthase gene were analyzed in wild Arachis species. Our aim was to expand the knowledge about resveratrol in Arachis, analyzing species from five sections and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 60 publications
(86 reference statements)
2
17
0
Order By: Relevance
“…Although one of the most adopted strategies for stress-induced priming in plants, few studies have addressed the reprogrammed transcriptional responses after UV-C exposure from a transcriptomic point of view [ 8 , 19 , 20 ]. Recently, our group demonstrated that wild Arachis plants exposed to UV-C produce high levels of resveratrol, which is associated with the induced expression of resveratrol synthase genes [ 21 ]. Cultivated peanut ( Arachis hypogaea ) and its wild relatives are among the few plants that naturally synthesize resveratrol, an important phytoalexin selectively accumulated in response to pathogen attack [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one of the most adopted strategies for stress-induced priming in plants, few studies have addressed the reprogrammed transcriptional responses after UV-C exposure from a transcriptomic point of view [ 8 , 19 , 20 ]. Recently, our group demonstrated that wild Arachis plants exposed to UV-C produce high levels of resveratrol, which is associated with the induced expression of resveratrol synthase genes [ 21 ]. Cultivated peanut ( Arachis hypogaea ) and its wild relatives are among the few plants that naturally synthesize resveratrol, an important phytoalexin selectively accumulated in response to pathogen attack [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study investigated the global transcriptomic changes induced by UV exposure in detached leaves of A. stenosperma to understand better the molecular mechanisms involved in activating plant defense responses to primary stress events and the potential acquisition of a priming state. Detached leaves have long been successfully used as explants for transcriptomic, proteomic, and metabolomic analysis of stress responses induced by UV exposure in leaves of cultivated and wild Arachis species [ 21 , 22 , 30 , 31 ], as well as in several plant species, including grapevine [ 32 , 33 ], soybean [ 34 ], Polygonum cuspidatum [ 35 ], Arabidopsis thaliana [ 36 ], spinach [ 37 ], rice [ 38 ], and maize [ 39 ]. The controlled environment of detached-leaf assays can overcome limitations imposed by field and greenhouse evaluations conducted with whole plants, allowing more standardized assessments and improving the number and homogeneity of samples that could be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the concentration of Acid Detergent Fiber (ADF) is widely varies its range from 21% to 41% in dry matter (Hess et al, 2003). This plant has possesses a number of secondary metabolites including sterols, flavonoids, phenolic acids, triterpenes, alkaloids, fatty acid and resveratrol (Carvalho et al, 2020;Tien et al, 2020). Resveratrol is an important bioactive compound having antioxidant properties (Carvalho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This plant has possesses a number of secondary metabolites including sterols, flavonoids, phenolic acids, triterpenes, alkaloids, fatty acid and resveratrol (Carvalho et al, 2020;Tien et al, 2020). Resveratrol is an important bioactive compound having antioxidant properties (Carvalho et al, 2020). This bioactive compound (resveratrol) is used as a therapeutic agent for the prevention of treatment of various diseases such as neoplastic, metabolic, cardiovascular, pulmonary as well as neurological disorder (Carvalho et al, 2020;Yang et al, 2016;Meng et al, 2014;Harikumar and Aggarwal, 2008) In India, the species is distributed in forests of Goa, Karnataka, Kerala, Maharashtra, Tamil Nadu, Sikkim and West Bengal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation